1994
DOI: 10.1017/s0003356100007698
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofSaccharomyces cerevisiaeyeast culture supplement on ruminal metabolism in buffalo calves given a high concentrate diet

Abstract: The effect of inclusion of live yeast culture (YC, Saccharomyces cerevisiae plus growth medium) in a high concentrate diet given to buffalo (Bubalus bubalis) calves on the rumen microbial population and fermentation pattern and in sacco dry matter disappearance of dietary constituents was examined. Six rumen-fistulated buffalo calves of about 120 kg live iveight were divided into two equal groups. The control group was given a diet consisting of, on a dry-matter basis, 0·90 kg ivheat straw, 1 kg berseem (Trifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 18 publications
5
29
1
3
Order By: Relevance
“…However, in gnotobiotically-reared lambs harbouring a very simplified rumen microflora, ammonia concentration was decreased in the presence of ADY (Chaucheyras-Durand & Fonty, 2001), this phenomenon being also observed in the rumen of newborn conventional lambs (Chaucheyras-Durand & Fonty, 2002). In another study with adult ruminants, the same effect on ammonia concentration was observed with daily supplementation by a YC (Kumar et al, 1994). These data suggested some changes in the nitrogen metabolism of rumen microorganisms in the presence of yeasts.…”
Section: Effects On Nitrogen Metabolismsupporting
confidence: 54%
“…However, in gnotobiotically-reared lambs harbouring a very simplified rumen microflora, ammonia concentration was decreased in the presence of ADY (Chaucheyras-Durand & Fonty, 2001), this phenomenon being also observed in the rumen of newborn conventional lambs (Chaucheyras-Durand & Fonty, 2002). In another study with adult ruminants, the same effect on ammonia concentration was observed with daily supplementation by a YC (Kumar et al, 1994). These data suggested some changes in the nitrogen metabolism of rumen microorganisms in the presence of yeasts.…”
Section: Effects On Nitrogen Metabolismsupporting
confidence: 54%
“…These results were supported by the finding of Kumar et al (1994). In the contrary, Agarwal et al (2002) observed no effect of probiotic feeding on the log number of cells of lactic acid bacteria, yeast and coliform bacteria in the faeces and rumen liquor of calf at any age when 100 g fermented feed was fed to the animals containing S. cerevisiae NCDC-49 at 10 6 cfu/ml.…”
Section: Resultsmentioning
confidence: 65%
“…The modifications reported in the literature on the in situ degradation of forage cell walls induced by probiotics range widely and are generally non-significant [13,15,16,25,33,43,44]. For example, Wallace et al [46] indicated that the rate of degradation was stimulated by SC while the maximum level of degradation was not influenced.…”
mentioning
confidence: 99%